Formulation and characterization of tretinoin nanosuspension and in silico testing as an anti-inflammatory - Ramadhoni, M Ayodia; Jafar, Garnadi; Halizah, Arin Nur; Fatmawati, Fenti (Institute of Computer Science (IOCS), 2025)
Introduction: Tretinoin is an effective retinoid derivative for acne therapy, but has formulation challenges due to its lipophilic nature and high crystallinity. An appropriate formulation strategy is needed to improve its stability and bioavailability. Objective: This study aims to evaluate the compatibility of tretinoin with excipients in nanosuspension formulations and their physicochemical characterization. Methods: Preliminary tests were carried out using Fourier Transform Infrared Spectroscopy (FTIR), crystallinity was analyzed by X-ray Diffraction (XRD), and thermal analysis by Differential Scanning Calorimetry (DSC). Nanosuspension characterization includes particle size, polydispersity index, zeta potential and entrapment efficiency. In silico test of the potential of tretinoin as a COX-2 inhibitor related to anti-inflammatory effects. Results: FTIR results showed no chemical interaction between tretinoin and excipients. XRD showed a decrease in tretinoin crystallinity after mixing with HPMC and PVP. DSC showed a shift in the melting point of tretinoin, indicating a physical interaction with excipients. Characterization of nanosuspension showed particle size <1000 nm, polydispersity index <0.5, zeta potential ±-20 mV, and entrapment efficiency >80%. In silico tests show that tretinoin has a binding energy of -9.57 kcal/mol against the Cyclooxygenase-2 (COX-2) enzyme with an inhibition constant of 96.03 nM. Conclusion: Tretinoin shows good compatibility and physicochemical characteristics in nanosuspension formulation, as well as potential as an anti-inflammatory agent through COX-2 inhibition.